1999
DOI: 10.1046/j.1365-313x.1999.00523.x
|View full text |Cite
|
Sign up to set email alerts
|

CYP78A5 encodes a cytochrome P450 that marks the shoot apical meristem boundary in Arabidopsis

Abstract: SummaryThe normal development of shoot structures depends on controlling the growth, proliferation and differentiation of cells derived from the shoot apical meristem. We have identi®ed the CYP78A5 gene encoding a putative cytochrome P450 monooxygenase that is the ®rst member of the CYP78 family from Arabidopsis. This gene is strongly expressed in the peripheral regions of the vegetative and reproductive shoot apical meristems, de®ning a boundary between the central meristematic zone and the developing organ p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
73
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 50 publications
2
73
0
1
Order By: Relevance
“…Both genes are expressed at the periphery of the meristem proper and at the base of new leaf primordia (Zondlo and Irish, 1999;Miyoshi et al, 2004;Anastasiou et al, 2007). We found that CYP78A5 loss-of-function mutants had shortened plastochrons in both long and short days.…”
Section: Effects Of Cyp78a5/kluh and Cyp78a7 On Plastochron Lengthmentioning
confidence: 72%
See 2 more Smart Citations
“…Both genes are expressed at the periphery of the meristem proper and at the base of new leaf primordia (Zondlo and Irish, 1999;Miyoshi et al, 2004;Anastasiou et al, 2007). We found that CYP78A5 loss-of-function mutants had shortened plastochrons in both long and short days.…”
Section: Effects Of Cyp78a5/kluh and Cyp78a7 On Plastochron Lengthmentioning
confidence: 72%
“…By comparing endogenous expression domains of SPL genes with the results of misexpression studies, we demonstrate that miR156 limits plastochron length in developing leaf primordia. The effects of miR156/SPLs on leaf initiation rate appear to be independent of CYP78A5/KLUH, a likely ortholog of rice PLA1 (Itoh et al, 1998;Zondlo and Irish, 1999;Miyoshi et al, 2004;Anastasiou et al, 2007). Interestingly, organ size and plastochron length are coordinately affected by both miR156/SPL and CYP78A5, suggesting either that there are common regulators of organ size and plastochron length or that these two developmental parameters reciprocally influence each other.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…This phenotype included large siliques and short stamens, a delay in bud opening and organ abscission, reduced fertility, a more severe phenotype in basipetal flowers, and longevity. This shared phenotype between the different genes indicates that they might act on a related metabolic network (Zondlo and Irish, 1999;Ito and Meyerowitz, 2000;Marsch-Martinez et al, 2002;Fang et al, 2012). An insertional knockout line for KLUH/ CYP78A5 showed a higher rate of leaf initiation (Wang et al, 2008).…”
mentioning
confidence: 94%
“…Although the catalytic function of the Arabidopsis CYP78A enzymes remains unknown, the expression pattern and the in vivo effect of the related genes bring up their possible engagement in the biosynthesis of some unknown type of plant growth regulator (Zondlo and Irish, 1999;Ito and Meyerowitz, 2000;Anastasiou et al, 2007;Kai et al, 2009).…”
mentioning
confidence: 99%